Anthropometric profile, body composition, and somatotype in stand-up paddle (SUP) boarding international athletes a cross-sectional study - Castañeda Babarro, A.; Viribay Morales, A.; León Guereño, P.; Mielgo-Ayuso, J.; Urdampilleta, A.; Coca Núñez, A. (Nutrición Hospitalaria, 2020)
Introduction: the anthropometric characteristics of international stand-up paddle (SUP) boarders are relevant aspects when it comes to their performance. However, very little research has been carried out within this sport, almost none regarding the body composition and anthropometric characteristics of SUP practitioners. Therefore, the aim of this research will be to describe the anthropometric profile of international SUP boarders.